Affiliative and Aggressive Humor in Leadership and Mechanism to Creativity and Employee Well Being Via LMX - Rahmat, Adi (SAINS ORGANISASI, 2023)
This study aims to determine the mediation of LMX on the influence of leadership humor which consists of affiliative and aggressive humor, on the mechanism of creativity of subordinates and employee welfare at the Colleges of Economics in Pekanbaru City. This study uses a quantitative approach with the PLS Structural Equational Modeling (SEM) statistical test method. Respondents in this study were all lecturers at the College of Economics in Pekanbaru City. The total population in this study was 173 lecturers spread over 7 Colleges of Economics in Pekanbaru City which were taken using a total sampling technique. This study found that humor leadership has a significant direct effect on leader member exchange, follower's creativity and wellbeing. In addition, humor leadership indirectly affects follower's creativity and well-being through the mediation of leader member exchange. In general, our information set preferably: It makes a direct effect of positive humor styles on pioneers on devotees' prosperity and innovativeness. In addition, this starts this relationship to be more grounded for subordinates with a low power distance direction. What's more, we started interceding properties that were directed through LMX as guessed for all result factors. To begin with, it could be essential to explore the methodology by which positive humor styles in pioneers uncover, eventually, impact adherent imagination and prosperity as do other progressive social variables. From one viewpoint, our outcomes recommend that social methodology might be a method for changing the effect of positive humor styles on pioneers. Although it may be ubiquitous, the phenomenon has received relatively little attention by organizational scholars, perhaps because of its frivolous and playful nature, and because it appears to contrast with the norms of rationality espoused in modern business, education, and government organizations.